Targeting accuracy of neuronavigation: a comparative evaluation of an innovative wearable AR platform vs. traditional EM navigation - Carbone, Marina; Montemurro, Nicola; Cattari, Nadia; Autelitano, Martina; Cutolo, Fabrizio; Ferrari, Vincenzo; Cigna, Emanuele; Condino, Sara (Frontiers in Digital Health, 2025)
Wearable augmented reality in neurosurgery offers significant advantages by enabling the visualization of navigation information directly on the patient, seamlessly integrating virtual data with the real surgical field. This ergonomic approach can facilitate a more intuitive understanding of spatial relationships and guidance cues, potentially reducing cognitive load and enhancing the accuracy of surgical gestures by aligning critical information with the actual anatomy in real-time. This study evaluates the benefits of a novel AR platform, VOSTARS, by comparing its targeting accuracy to that of the gold-standard electromagnetic (EM) navigation system, Medtronic StealthStation® S7®. Both systems were evaluated in phantom and human studies. In the phantom study, participants targeted 13 predefined landmarks using identical pointers to isolate system performance. In the human study, three facial landmarks were targeted in nine volunteers post-brain tumor surgery. The performance of the VOSTARS system was superior to that of the standard neuronavigator in both the phantom and human studies. In the phantom study, users achieved a median accuracy of 1.4 mm (IQR: 1.2 mm) with VOSTARS compared to 2.9 mm (IQR: 1.4 mm) with the standard neuronavigator. In the human study, the median targeting accuracy with VOSTARS was significantly better for selected landmarks in the outer eyebrow (3.7 mm vs. 6.6 mm, p = 0.05) and forehead (4.5 mm vs. 6.3 mm, p = 0.021). Although the difference for the pronasal point was not statistically significant (2.7 mm vs. 3.5 mm, p = 0.123), the trend towards improved accuracy with VOSTARS is clear. These findings suggest that the proposed AR technology has the potential to significantly improve surgical outcomes in neurosurgery.